Water availability periods and soil moisture during extreme years of crop production at Solapur - RAO, G. APPA; BHIDE, B. A. (MAUSAM, 1980)
Analysis has been carried out to obtain different water availability periods during extreme rabi sorghum yields at Solapur. They are humid, moist and preparatory periods computed on the basis of weekly rainfall and potential evapotranspiration. It is observed that low yields occur due to shorter period of moist and humid type and are generally associated with higher positive aridity anomalies during sowing, tillering and flowering stages of the crop. Weekly water budgeting indicated that the soil moisture variations are significant in extreme years of crop output. Probabilities of different soil moisture ranges showed the possibility of shifting the sowing date backward for a better yield, which is supported by special field experiments conducted at Solapur.